Frontispiece: Functionalized Membranes for Photocatalytic Hydrogen Production. Issue 45 (3rd November 2014) - Troppmann, Stefan; König, Burkhard
<x xml:space="preserve">Abstract</x> Supramolecular Chemistry The design of artificial systems for solar energy conversion mimicking natural photosynthesis is a major scientific challenge. In their Communication on page 14570 ff. B. König and S. Troppmann show the preparation of functionalized membranes for photocatalytic hydrogen generation in water by co‐embedding of an amphiphilic photosensitizer and a water reduction catalyst into vesicular bilayers. In these noncovalent self‐assemblies, the dynamic two‐dimensional reorganization of the embedded catalytic subunits in fluid membranes plays an important role for the light‐driven hydrogen production.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>